Migranticization - Dahinden, Janine (Edward Elgar Publishing, 2025)
Migranticization can be understood as those sets of performative practices that ascribe a migratory status to certain people and bodies – labelling them (im)migrants, second-generation migrants, people with migration background, minorities, etc. – and thus (re-)establish a priori difference to non-migrant citizens: regardless of whether the people designated as migrants are citizens of the nation-state they reside in or not, and regardless of whether they have crossed a national border or not. Migranticization can be considered as a technology of power and governance; it places people in a distinct hierarchy which goes along with an unequal distribution of societal symbolic and material resources while it affirms a national we within a system of global inequalities. The suggestion is to use migranticization as an analytical lens which makes it possible to investigate the uses of migration-related categories and their consequences in terms of power and ex/inclusion from/in a global system of inequalities and nation-states.